Timber Properties and Cellulose Crystallites Size in Pine Wood Cut in Different Sawing Patterns after Pretreatment with CH3COOH and H2O2 and Densification - Andi Detti Yunianti (MDPI AG, 2021)
One process to improve wood quality is densification or wood surface compression. Our study analyzed the changes in some basic properties of pine wood, including its anatomical structure, density, modulus of elasticity (MOE), and dimensions of cellulose crystallites, after densification following soaking pretreatment in CH3COOH and H2O2 at a concentration of 20%. Samples were sawn in radial and tangential directions for analysis of the wood. The results showed a change in the shape of tracheid cells from hexagonal to oval, as well as damage to the ray cell constituents on the tangential surface. The thickness decrease of the samples was in accordance with the target, which meant that spring-back was short. In general, the tangential boards had a higher density than the radial boards, with a lower MOE and crystallite dimensions. Our findings showed that the densified tangential board was stronger than the radial board.